Analyzing Nonmelanoma Skin Cancer Using Enzyme‐Activatable Two‐Photon Probes. (20th November 2020) - Lim, Chang Su; Choi, Jee Woong; Kim, You Chan; Kim, Hwan Myung
Abstract : In this study, we attempted to diagnose nonmelanoma skin cancer (NMSC) more accurately by two‐photon microscopy imaging deep inside of skin tissue using a two‐photon probes that can detect three enzyme activities.